2011
DOI: 10.1080/02640414.2011.591421
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory strategies of team-handball goalkeepers

Abstract: This study seeks to discover whether handball goalkeepers employ a general anticipatory strategy when facing long distance throws and the effect of uncertainty on these strategies. Seven goalkeepers and four throwers took part. We used a force platform to analyse the goalkeeper's movements on the basis of reaction forces and two video cameras synchronised at 500 Hz to film the throw using 3D video techniques. The goalkeepers initiated their movement towards the side of the throw 193 ± 67 ms before the release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
3
11
0
2
Order By: Relevance
“…The results obtained (Table 2) show very similar values to those shown by elite TH players, being higher than those found in the wings, and lower than the backs (Vila et al, 2012). Throwing velocity is a determining factor for performance in handball (Gutierrez-Davila, Rojas, Ortega, Campos, & Parraga, 2011). The values obtained in this study are higher than those obtained in other studies with TH players in throws from stop and 3-step runs (Granados et al, 2007;Vila et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…The results obtained (Table 2) show very similar values to those shown by elite TH players, being higher than those found in the wings, and lower than the backs (Vila et al, 2012). Throwing velocity is a determining factor for performance in handball (Gutierrez-Davila, Rojas, Ortega, Campos, & Parraga, 2011). The values obtained in this study are higher than those obtained in other studies with TH players in throws from stop and 3-step runs (Granados et al, 2007;Vila et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the success of expert goalkeepers in save actions seems to be located in the delayed start into save movement in order to obtain more information about the ball's trajectory and in executing intervention actions in a shorter time (faster) than their less experienced colleagues (Schorer, 2005). Such findings reinforce the importance of goalkeepers' training aiming at the development of maximum strength and explosive strength (Aagaard, Simonsen, Andersen, Magnusson, & Dyhre-Poulsen, 2002) and their ability to anticipate actions by identifying signals sent by attackers on the side and height of a throw on goal to decrease uncertainty (Guttiérrez-Davila, Rojas, Ortega, Campos, & Párraga, 2011;Rojas, Gutiérrez-Davila, Ortega, Campos, & Párraga, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Our results could lead to some practical implications. Recently, behavioral analysis of seven handball goalkeepers in a lab-context demonstrated that they had to employ an anticipatory strategy when facing long distance throws (Gutierrez-Davila et al, 2011). In the present study, the distinctive micro-decisions we found provide support for re-thinking goalkeepers training in handball, or even in other team sports such as soccer and hockey.…”
Section: Practical Implicationssupporting
confidence: 63%